Scoping review: safety and risk in aesthetic preference determinants for product design - Cheng, Si; Yahaya, Mohd Faiz; Abd Rahman, Ahmad Rizal; Tai, Lichen (MAK HILL Publications, 2024)
Designers should aim at resolving newness kinds of creativity that entail a tension between‐metaphorically speaking‐needs for safety and risky in order to arrive at a beautiful design. The Unified Model of Aesthetics suggests aesthetic preference for safety and risky, using principles of unity‐in‐variety, most advanced, yet acceptable and autonomous, yet Connected. However, there is a lack of evidence on the component framework of safety and risky of aesthetic pleasure and its overall determinants, especially in products design. the current review sought to understand the main determinants of aesthetic pleasure for safety and risky to predict the indicators of Perceptual, Cognitive and Social components in products design. a scoping review is conducted by reviewing English language literature published between 2011 and 2023 in three electronic databases, including Scopes, Science Direct and Emerald, using keywords and inclusion and exclusion criteria. the current study conducts a scoping review of the existing studies that indicate various determinate of unity and variety, typicality and novelty, connectedness and autonomy in aesthetic preference in order to identify the related indicators of safety and risky in product design. this scoping review contributed to the identification of comprehensive indicators of aesthetic pleasure for safety and accomplishment in products design.